2007
DOI: 10.1111/j.1460-9568.2007.05498.x
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor exercise alters expression of pro‐brain‐derived neurotrophic factor, brain‐derived neurotrophic factor and its receptor TrkB in the spinal cord of adult rats

Abstract: Previous evidence indicates that locomotor exercise is a powerful means of increasing brain-derived neurotrophic factor (BDNF) and its signal transduction receptor TrkB mRNA levels, immunolabeling intensity and number of BDNF- and TrkB-immunopositive cells in the spinal cord of adult rats but the contribution of specific cell types to changes resulting from long-term activity is unknown. As changes in BDNF protein distribution due to systemic stimuli may reflect either its in-situ synthesis or its translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 73 publications
7
47
2
Order By: Relevance
“…Exercise increases BDNF in the brain (Berchtold, et al, 2005) and spinal cord (Gomez-Pinilla, et al, 2002, Zaheer, et al, 2006. Exercise also up regulates the BDNF receptor trkB (Macias, et al, 2007). Therefore, it is tempting to speculate that neurotrophins are involved in the enhanced axon elongation associated with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise increases BDNF in the brain (Berchtold, et al, 2005) and spinal cord (Gomez-Pinilla, et al, 2002, Zaheer, et al, 2006. Exercise also up regulates the BDNF receptor trkB (Macias, et al, 2007). Therefore, it is tempting to speculate that neurotrophins are involved in the enhanced axon elongation associated with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, retrograde transport of NT-4 from the target could not be demonstrated in these preganglionic neurons, and thus the exact mechanisms involved in the NT-4-mediated survival of the lower intermediolateral cell column are not known. Preganglionic neurons located in the IML of the upper thoracic cord may be regulated by brain-derived neurotrophic factor (BDNF) , though these phenomena have not been well documented.In addition to preganglionic neurons, trkB-ir glial cells have been reported in the motor areas of the lumbar spinal cord [19] and were shown to be altered by exercise [13]. The extent to which the trkB-ir glial cells were present in the upper thoracic cord has not been described.…”
mentioning
confidence: 97%
“…Whether the anatomical relationship observed in the current study represents a similar interaction or a previously undescribed relationship is unknown at present. Though Macias et al [13] showed numerous trkB-ir glial cells surrounding large ventral horn motoneurons in the lumbar spinal cord, a potential interaction between these two cell types was not discussed. In the current study, no obvious differences in the number of these cells were observed following NGF administration.…”
mentioning
confidence: 99%
“…Whole hippocampal homogenates were separated by 15% PAGE and processed for Western blot analysis using rabbit anti-BDNF (1:1,000; SC546; Santa Cruz) followed by ECL Plus (Amersham) and quantified (11). The BDNF antisera detects distinct pro BDNF and mBDNF bands as described (11,35,36). Recombinant human BDNF (Chemicon) was added as positive control.…”
Section: (Si Text)mentioning
confidence: 99%